Rollercoasters and research: applying data-enabled design to a semi-public context - Raviselvam, Sujithra; Lovei, Peter; Noortman, Renee; Olsson, Thomas; Väänänen, Kaisa; Funk, Mathias (Frontiers in Human Dynamics, 2024)
Data-enabled design (DED) is a design approach where research data is integrated with design praxis in an iterative and hands-on fashion, and it has been successfully applied to design for people in the healthcare domain. However, how to utilise DED as a more broadly applicable approach that facilitates design for larger populations in semi-public spaces remains an open question. Understanding the advantages and challenges of applying DED in various contexts is crucial to guide design researchers further and prevent methodological mismatch. In this article, we report on applying DED in an open, semi-public context with a large population of visitors. Here, DED was applied in projects with student design researchers who had limited control over the data gathered from people in the context. We share the results of a two-week design workshop that involved sixteen student design researchers and was organised in collaboration with Särkänniemi, one of Finland's largest theme parks. Using design proposals and reflections from five teams, we investigate the use of DED in this context, reporting on perceived challenges, barriers, successes and future directions for taking the DED approach into similar (semi-)public contexts. We conclude with reflections from the workshop organisers' point of view and share the feedback from our industry collaborator, highlighting challenges and opportunities in translating the DED approach to a new domain.